Aurora rising - Kaufman, Amie; Kristoff, Jay (The Aurora cycle, 2019)
Told in separate voices, eighteen-year-old Tyler Jones, top graduate of Aurora Academy, and a group of misfits and troublemakers embark on their first mission with Auri, a stowaway from the distant past.